A case report of a pregnant woman infected with coronavirus disease 2019 pneumonia. Issue 30 (24th July 2020) - Peng, Jing; Li, Ruobing; Yin, Heng; Tang, Fei; Xie, Hui; Li, Min; Zhao, Yun
Abstract: Rationale: Since the end of December 2019, the outbreak of coronavirus disease 2019 (COVID-19) epidemic has occurred and spread rapidly throughout China. At present, China's epidemic situation has been basically controlled, but the number of cases worldwide is increasing day by day. On March 11, the WHO officially announced that the COVID-19 had become a global pandemic. However, there are currently limited data on pregnant women with COVID-19 pneumonia and their infants. In this paper, a case of a pregnant woman infected with COVID-19 pneumonia is reported. Patient concerns: We report a clinically confirmed COVID-19 pregnant woman. The patient was tested negative 4 times in nucleic acid test, but immunoglobulin G was positive and immunoglobulin M was negative before delivery, suggesting a previous infection. Diagnoses: The pregnant woman underwent a computed tomography scan of both lungs at 29 + 2 weeks of pregnancy, and scattered stiffness and frosted glass shadows of both lungs were observed. According to the diagnostic criteria for COVID-19 pneumonia in the "New Coronavirus Prevention and Control Plan Fifth Edition" of the National Health Commission of China, she was diagnosed as a clinically confirmed case. Interventions: The pregnant women received nebulized inhalation and oral cephalosporin treatment in a community hospital and was discharged after the symptoms disappeared. After that, she was isolated at home. Outcomes: The pregnant woman gave birth to a healthy baby after being cured from COVID-19 infection. The nucleic acid test of the neonatal pharyngeal swab was negative, and the neonatal serum test showed positive for immunoglobulin G and negative for immunoglobulin M. Lessons subsections: The findings of this case report are useful for understanding the possible clinical features of COVID-19 infection in pregnant women, the duration of the antibody, and passive immunity of the fetus.